Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Organic electron donor limitation triggers metabolic trade-offs in anaerobic granular sludge: The pivotal role of Fe-mediated electron bifurcation - Bochuang Huang; Yangyang Li; Jinhao Zhu; Juncong Zou; Dexin Wang; Chunping Yang; Hongjun Han; Wencheng Ma (Chemical Engineering Journal, 2026)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Cobalt-doped zinc phosphides regulated by phytic acid effects on the electrochemical activity of sensing clothianidin - Peiyuan Wei; Wei Han; Lingling Xie; Hongjun Chen; Yuling Wang; Limin Zhu; Baoshan He; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Reversing inhibition to promotion in phenol-ammonium metabolism via algal-microbial fuel cell: Mechanisms of phenol-ammonium interaction and synergistic removal - Yaqi Liu; Mengqi Zheng; Longyi Lv; Guowei Chen; Chengye Wang; Zhenhu Hu; Jingwei Feng; Binghan Xie; Hongjun Han; Wei Wang (Journal of Hazardous Materials, 2025)

High Yield of Prodigiosin by Serratia marcescens Ka3 Using Additive Huangshui, a Byproduct of Chinese Liquor (Baijiu) - Chuan Wang; Zhongxing Gao; Rui Han; Yaomei Tian; Hongjun Fan; Yuliang Zhang (Current Microbiology, 2025)

Natural variations in the promoter of ZmDeSI2 encoding a deSUMOylating isopeptidase controls kernel methionine content in maize - Xin Lu; Yuhong Lei; Zhennan Xu; Zixiang Cheng; Meng Liu; Yuxin Tai; Xiaohua Han; Zhuanfang Hao; Mingshun Li; Degui Zhang; Hongjun Yong; Jienan Han; et al. (Molecular Plant, 2025)

Unveiling environmental adaptability of magnetite-mediated Feammox system: Multiple pathways identification, metabolic responses and engineering potential analysis - Xiangzhuang Fu; Yangyang Li; Weiwei Huang; Dexin Wang; Chunping Yang; Hongjun Han (Chemical Engineering Journal, 2025)

Molecular characterization of large yellow croaker (Larimichthys crocea) coagulation factor Ⅶ-like and its function on macrophage proliferation and polarization - Yueming Chen; Han Zhao; Shuangshuang Cao; Hongjun Xie; Jieyu Huang; Xinhua Chen; Zhengwei Cui (Fish & Shellfish Immunology, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Optimization scheduling of household integrated energy systems for improving thermal comfort with low cost - Yunlong Wang; Lu Han; Xinlong Deng; Hongjun Gao (Energy and Buildings, 2025)

Astral-based DIA proteomics explored the flavor enhancement mechanism of Chinese traditional smoked bacon by staphylococcal co-fermentation - Li Yang; Hongjun Li; Han Wu; Xueling Sun; Shuyun Liu; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

New insights into the improved contaminants removal in SBR by intermittently weak ultrasound - Jingshen Zhang; Jinlin Wang; Guirong Li; Shengyong Jia; Hongjun Han; Fengchang Wu; Yuanhu Pei (Chemosphere, 2024)

Enhanced removal of quinoline and nitrate in synthetic photovoltaic wastewater by non-aerating algae-bacteria symbiosis system: Microbial environmental response and nitrogen metabolism - Zipeng Yan; Mengqi Zheng; Yan Wang; Hao Shen; Yaqi Liu; Jie Wang; Hong Mei; Yuying Du; Yantao Zhou; Kuizu Su; Hongjun Han (Journal of Water Process Engineering, 2024)

Response of soil gross nitrogen mineralization to fertilization practices in China's uplands - Jun Wang; Yinghua Duan; Guanmo Li; Lu Zhang; Dejin Li; Kailou Liu; Xi'an Cui; Boku Zhou; Hongjun Gao; Xiaori Han; Junyong Ma; Shutang Liu; et al. (Journal of Cleaner Production, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Which biofilm reactor is suitable for degradation of 2,4-dimethylphenol, focusing on bacteria, algae, or a combination of bacteria-algae? - Jingxin Shi; Ning Wan; Shuhui Yang; Yuanyuan Yang; Hongjun Han (Journal of Hazardous Materials, 2024)

Unraveling the mechanism of aroma loss during prolonged hot air drying of non-smoked bacon: Insights into aroma compounds generation and retention - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2024)

Unraveling the influence of lipids on aroma generation in non-smoked bacon during boiling through untargeted lipidomics analysis - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2024)

The development of an emotion lexicon for spicy food flavor experience - Lina Ren; Risu Na; Siyi Jiang; Darong Chen; Li Zhang; Hongjun Li; Pengfei Han (International Journal of Gastronomy and Food Science, 2024)

Insights into microbial metabolic coordination under driving force of different conductive materials-mediated direct interspecies electron transfer during anaerobic digestion - Xinwei Zhou; Mengxia Guo; Xiangzhuang Fu; Dexin Wang; Jianjun Liao; Wen Xu; Hongjun Han (Chemical Engineering Journal, 2024)

New insights into the dominance of mixed fermentation of Staphylococcus cohnii and Staphylococcus saprophyticus in Chinese bacon: Complete genomic and comparative genomic perspectives - Li Yang; Hongjun Li; Han Wu; Xuelian Sun; Shuyun Liu; Dong Zhang; Chang Su; Zhifei He (Food Research International, 2024)

Quantitative proteomic analysis to identify potential biomarkers linked to quality traits of beef tripe from different sources - Xuelian Sun; Zhifei He; Li Yang; Han Wu; Hongjun Li (Food Chemistry, 2024)

Effect of heme proteins on the lipid molecule profile and aroma formation during hot air drying of non-smoked bacon - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Exploring potential lipid precursors for aroma formation in non-smoked bacon during hot air drying via untargeted lipidomics and oxidation model - Han Wu; Zhifei He; Li Yang; Hongjun Li (Meat Science, 2024)

Microbiological interpretation of weak ultrasound enhanced biological wastewater treatment – using Escherichia coli degrading glucose as model system - Shengyong Jia; Yanfang Diao; Yingying Li; Jingshen Zhang; Hongjun Han; Guirong Li; Yuanhu Pei (Bioresource Technology, 2024)

Effect of staphylococci fermentation and their synergistic Lactobacillus on the physicochemical characteristics and nonvolatile metabolites of Chinese bacon - Li Yang; Hongjun Li; Han Wu; Shuyun Liu; Zhifei He (Meat Science, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

An efficient solution based on the synergistic effects of nickel foam in NiFe-LDH nanosheets for oil/water separation - Xinchun Lu; Liguo Shen; Hongjun Lin; Lei Han; Jiarong Du; Cheng Chen; Jiaheng Teng; Bisheng Li; Wei Yu; Yanchao Xu (Journal of Hazardous Materials, 2024)

Biotoxicity dynamic change and key toxic organics identification of coal chemical wastewater along a novel full-scale treatment process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

Highly efficient and selective electrosynthesis of urea via co-reduction of carbon dioxide and nitrate over the TiN catalyst - Hongjun Fang; Ze Wang; Chen-Han Kuo; Hongsheng Yang; Xinzhen Feng; Weijie Ji; Chak-Tong Au (Chemical Engineering Journal, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Generation of key aroma compounds in fat and lean portions of non-smoked bacon induced via lipid pyrolysis reaction - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Staphylococcus inoculation enhances the sensorial attributes of Chinese bacon by coordinating the composition of flavor compounds through amino acid metabolism - Li Yang; Hongjun Li; Han Wu; Shunyun Liu; Zhifei He (Food Research International, 2024)

Mxenes for membrane separation: from fabrication strategies to advanced applications - Zhengyi Huang; Die Ling Zhao; Liguo Shen; Hongjun Lin; Cheng Chen; Yanchao Xu; Bisheng Li; Jiaheng Teng; Lei Han; Tai-Shung Chung (Science Bulletin, 2024)

Overview of enhancing biological treatment of coal chemical wastewater: New strategies and future directions - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Journal of Environmental Sciences, 2024)

Insights into synergistic metabolism of phenol and ammonium pollutants in treating coal gasification wastewater by algal-microbial fuel cell - Chengye Wang; Mengqi Zheng; Guowei Chen; Zipeng Yan; Binghan Xie; Wei Wang; Hongjun Han (Journal of Water Process Engineering, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Using automated machine learning techniques to explore key factors in anaerobic digestion: At the environmental factor, microorganisms and system levels - Yi Zhang; Zhangmu Jing; Yijing Feng; Shuo Chen; Yeqing Li; Yongming Han; Lu Feng; Junting Pan; Mahmoud Mazarji; Hongjun Zhou; Xiaonan Wang; Chunming Xu (Chemical Engineering Journal, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Novel strategy to enhance the biological treatment of coal chemical wastewater by nano-zero valent iron loaded fly ash-based activated carbon assisted activated sludge process - Weiwei Ma; Xiaoqi Zhang; Hongjun Han; Xueqing Shi; Qiaoping Kong; Tong Yu; Fei Zhao (Environmental Science and Pollution Research, 2023)

Titanium oxide nanotubes intercalated two-dimensional MXene composite membrane with exceptional antifouling and self-cleaning properties for oil/water separation - Qianqian Zeng; Die Ling Zhao; Liguo Shen; Hongjun Lin; Ning Kong; Lei Han; Cheng Chen; Jiaheng Teng; Chuyang Tang; Tai-Shung Chung (Chemical Engineering Journal, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

A novel flower-like nickel-metal-organic framework (Ni-MOF) membrane for efficient multi-component pollutants removal by gravity - Lei Han; Jing Ma; Hongjun Lin; Cheng Chen; Jiaheng Teng; Bisheng Li; Dieling Zhao; Yanchao Xu; Wei Yu; Liguo Shen (Chemical Engineering Journal, 2023)

Bibliometric analysis and mini-review of global research on pyroptosis in the field of cancer - Wenwen Wang; Wenhuizi Sun; Han Xu; Yao Liu; Chenlu Wei; Siqiao Wang; Shuyuan Xian; Penghui Yan; Jiajun Zhang; Hongjun Guo; Hengwei Qin; Jie Lian; et al. (Apoptosis, 2023)

Simulation of transport mechanism of radium isotopes in aquifer on the southern coast of Laizhou Bay - Yancheng Wang; Guangquan Chen; Hongjun Yu; Xingyong Xu; Yinqiao Zou; Wenqing Zhao; Weitao Han; Wenzhe Lyu; Zhen Cui; Runtian Ding (Acta Oceanologica Sinica, 2023)

Volatile compounds comparison and mechanism exploration of non-smoked traditional Chinese bacon in Southwestern China and Eastern China - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2023)

Deformation analysis of underwater shield tunnelling based on HSS model parameter obtained by the Bayesian approach - Yao Lu; Peng Yu; Yan Zhang; Jian Chen; Tao Liu; Han Wang; Hongjun Liu (Frontiers in Marine Science, 2023)
Deformation analysis and control of underwater large-diameter shield tunnels is a prerequisite for safe tunnel construction. Reasonable selection of constitutive model and its parameters is the key to accurately predicting the deformation induced by underwater shield tunnelling. In this paper, the finite element analysis of cavity expansion during the piezocone penetration test (CPTU) based on the hardening soil model with small strain stiffness (HSS) model was carried out, and the correlation model of the normalized cone tip resistance Q with the reference secant modulus E 50 ref and the effective internal friction angle φ ’ was established and verified using mini CPTU chamber test. Then, a Bayesian probability characterization approach for E 50 ref of silty clay based on CPTU was proposed. Furthermore, the deformation analysis of Jinan Yellow River tunnel crossing the south embankment was carried out to verify the reliability of the proposed approach. The good agreement between the field measurement and numerical simulation confirms that the parameters obtained by the Bayesian approach are reliable. Finally, a sensitivity analysis was performed to study the law of riverbed settlement induced by underwater large-diameter shield tunnelling. The results show that the increasing support pressure could effectively reduce the riverbed settlement, but there is an upper limit. The optimal support pressure of established model is between 0.45 MPa and 0.5 MPa. The uphill section causes greater riverbed settlement than the downhill section. Under the same condition, increasing buried depth and water level will lead to a more significant settlement.

Strontium isotopes in the Ordovician paleokarst reservoirs, Huanghua Depression, China - Jinning Zhang; Guomeng Han; Lixin Fu; Hongjun Li; Yuan Neng; Xiao Ma (Arabian Journal of Geosciences, 2023)

3D printing titanium dioxide-acrylonitrile-butadiene-styrene (TiO2-ABS) composite membrane for efficient oil/water separation - Lei Han; Liguo Shen; Hongjun Lin; Zhengyi Huang; Yanchao Xu; Renjie Li; Bisheng Li; Cheng Chen; Wei Yu; Jiaheng Teng (Chemosphere, 2023)

Quality relationship between smoked and air-dried bacon of Sichuan-Chongqing in China: Free amino acids, volatile compounds, and microbial diversity - Li Yang; Hongjun Li; Han Wu; Chang Su; Zhifei He (Food Research International, 2023)

Dissimilatory manganese reduction facilitates synergistic cooperation of hydrolysis, acidogenesis, acetogenesis and methanogenesis via promoting microbial interaction during anaerobic digestion of waste activated sludge - Linli Wang; Yangyang Li; Xuesong Yi; Fei Yang; Dexin Wang; Hongjun Han (Environmental Research, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Genomic selection to introgress exotic maize germplasm into elite maize in China to improve kernel dehydration rate - Hongjun Yong; Nan Wang; Xiaojun Yang; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; et al. (Euphytica, 2021)

Disrupted pathways from frontal-parietal cortex to basal ganglia and cerebellum in patients with unmedicated obsessive compulsive disorder as observed by whole-brain resting-state effective connectivity analysis – a small sample pilot study - Wei Liu; Minghui Hua; Jun Qin; Qiuju Tang; Yunyi Han; Hongjun Tian; Daxiang Lian; Zhengqing Zhang; Wenqiang Wang; Chunxiang Wang; Ce Chen; Deguo Jiang; et al. (Brain Imaging and Behavior, 2021)

Case study on wastewater treatment technology of coal chemical industry in China - Jingxin Shi; Chunyan Xu; Yuxing Han; Hongjun Han (Critical Reviews in Environmental Science and Technology, 2021)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Effect of five modified mass selection cycles on combining ability in two Chinese maize populations - Hongjun Yong; Juan Tang; Xinzhe Zhao; Fengyi Zhang; Zhiyuan Yang; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Jienan Han; Bo Peng; et al. (Euphytica, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Enhanced nitrogen removal of coal pyrolysis wastewater with low COD to nitrogen ratio by partial nitrification-denitrification bioprocess assisted with polycaprolactone - Zhengwen Zhang; Chunyan Xu; Dan Zhong; Yuxing Han; Hongjun Han; Mengqi Zheng; Hao Zhu (Environmental Science and Pollution Research, 2019)

Biological coupling process for treatment of toxic and refractory compounds in coal gasification wastewater - Jingxin Shi; Yuxing Han; Chunyan Xu; Hongjun Han (Reviews in Environmental Science and Bio/Technology, 2018)

Treatment of real coal gasification wastewater using a novel integrated system of anoxic hybrid two stage aerobic processes: performance and the role of pure oxygen microbubble - Haifeng Zhuang; Hongjun Han; Shengdao Shan (Environmental Science and Pollution Research, 2016)

Evaluation of diagnostic ratios of medium and serious weathered oils from five different oil sources - Shijie He; Chuanyuan Wang; Yantai Li; Hongjun Yu; Bin Han (Acta Oceanologica Sinica, 2016)

Biodegradation and Interaction of Quinoline and Glucose in Dual Substrates System - Peng Xu; Wencheng Ma; Hongjun Han; Baolin Hou; Shengyong Jia (Bulletin of Environmental Contamination and Toxicology, 2015)

Isolation of a Naphthalene-Degrading Strain from Activated Sludge and Bioaugmentation with it in a MBR Treating Coal Gasification Wastewater - Peng Xu; Wencheng Ma; Hongjun Han; Shengyong Jia; Baolin Hou (Bulletin of Environmental Contamination and Toxicology, 2015)

Enzymatic and biological characteristics of enolase in Brucella abortus A19 - Xiangan Han; Chan Ding; Hongjun Chen; Qinghai Hu; Shengqing Yu (Molecular Biology Reports, 2012)

Major histocompatibility complex class IIA and IIB genes of the spotted halibut Verasper variegatus: genomic structure, molecular polymorphism, and expression analysis - Hongjun Li; Lianxin Jiang; Jiabo Han; Hao Su; Qing Yang; Chongbo He (Fish Physiology and Biochemistry, 2011)

Development of combined biological technology for treatment of high-strength organic wastewater and results of case studies - Nanqi Ren; Aijie Wang; Hongjun Han; Fang Ma; Jie Ding; Yue Shi; Dan Zhao (Journal of Ocean University of China, 2006)